Chronic Otitis Media with Effusion Is Associated with Increased Risk of Secondary Speech Surgery. Issue 2 (August 2015) - Hanes, Lauren A.; Murphy, Amanda; Hatchette, Jill E.; Delorey, Raylene; Wilson, Kenneth L.; Hong, Paul; Bezuhly, Michael
<x xml:space="preserve">Abstract</x> Background: Velopharyngeal insufficiency and chronic otitis media with effusion following primary cleft palate repair can be attributed to persistent abnormalities in the levator and tensor veli palatini muscles, respectively. The purpose of this case-control study was to examine the association between otitis media with effusion requiring myringotomy tubes and the need for secondary speech surgery. Methods: Records of patients who underwent primary palatoplasty at the authors' institution from 1990 to 2006 were reviewed. Data included age at primary palatoplasty, sex, Veau classification, surgeon, number of postpalatoplasty myringotomy tube procedures, hearing loss, 22q deletion syndrome diagnosis, and fistula. The primary outcome was need for secondary speech surgery. Results: Of 249 patients meeting inclusion criteria, forty-four patients (17.7 percent) had secondary speech surgery recommended or performed. Univariate analysis revealed a significant association between Veau classification, 22q deletion syndrome diagnosis, and two or more myringotomy tube procedures with secondary speech surgery. Adjusting for multiple covariates, children requiring two or more myringotomy tubes were 2.55 times more likely to require secondary speech surgery than patients who required one or fewer myringotomy tubes procedures (95 percent CI, 1.24 to 5.21; p = 0.009). Conclusions: The authors demonstrate that chronic otitis media with effusion requiring two or more myringotomy tube procedures is associated with a significantly increased likelihood of requiring secondary speech surgery. Using otitis media with effusion as a clinical predictor for secondary velopharyngeal insufficiency could lead to early identification of at-risk patients in need of intensive speech therapy and timely secondary speech surgery. CLINICAL QUESTION/LEVEL OF EVIDENCE: Risk, III.